Probing into the Effects of Multiple Intelligence-based Activities (MIBAs): Iranian EFL Students’ Writing Performance in Focus - Madhkhan, Mozhgan; Salehi, Hadi; Tabatabaei, Omid; Talebinejad, Mohammad Reza (KMAN Counseling & Psychology Nexus, 2025)
The present inquiry examined the impact of Multiple Intelligence-based Activities (MIBAs) on male and female EFL students’ writing improvement. For this purpose, a quantitative quasi-experimental pretest/posttest design, with the independent variable (use of MIBAs) and the dependent variable (writing) was used. Sixty (37 females, 23 males) undergraduate Persian-speaking EFL students, who were taking classes in Jahad Daneshgahi of Isfahan University of Technology were selected from 100 volunteer students, and they were made homogeneous in terms of their proficiency level, through Oxford Quick Placement Test (OQPT) and they were divided into control and experimental groups in a non-random fashion. Moreover, IELTS writing test was administered as pretest and posttest to evaluate the participants’ writing improvement. They were taught in some courses based on logical-mathematical, bodily-kinesthetic, visual-spatial, verbal-linguistic, intrapersonal, interpersonal, naturalistic, and musical intelligence activities. Participants were asked to follow traditional writing learning methods in the control group. Findings showed the outperformance of students in experimental group concerning the effect of MIBAs on increasing written performance, but there was no significant gender difference.